Morphology, reproduction and diet in Australian and Papuan death adders (Acanthophis, Elapidae). - Richard Shine; Carol L Spencer; J Scott Keogh (PLoS ONE)
Death adders (genus Acanthophis) differ from most other elapid snakes, and resemble many viperid snakes, in their thickset morphology and ambush foraging mode. Although these snakes are widely distributed through Australia and Papua New Guinea, their basic biology remains poorly known. We report morphological and ecological data based upon dissection of >750 museum specimens drawn from most of the range of the genus. Female death adders grow larger than conspecific males, to about the same extent in all taxa (20% in mean adult snout-vent length,  =  SVL). Most museum specimens were adult rather than juvenile animals, and adult males outnumbered females in all taxa except A. pyrrhus. Females have shorter tails (relative to SVL) than males, and longer narrower heads (relative to head length) in some but not all species. The southern A. antarcticus is wider-bodied (relative to SVL) than the other Australian species. Fecundity of these viviparous snakes was similar among taxa (mean litter sizes 8 to 14). Death adders encompass a broad range of ecological attributes, taking a wide variety of vertebrate prey, mostly lizards (55%), frogs and mammals (each 21%; based on 217 records). Dietary composition differed among species (e.g. frogs were more common in tropical than temperate-zone species), and shifted with snake body size (endotherms were taken by larger snakes) and sex (male death adders took more lizards than did females). Overall, death adders take a broader array of prey types, including active fast-moving taxa such as endotherms and large diurnal skinks, than do most other Australian elapids of similar body sizes. Ambush foraging is the key to capturing such elusive prey.